Banking Beyond Banks and Money A Guide to Banking Services in the Twenty-First Century
Banking Beyond Banks and Money A Guide to Banking Services in the Twenty-First Century / Paolo Tasca, ... .- [Place of publication not identified] : Springer International , 2016 .- 316 p. ; 23 cm .- 9783319424460